Teachers’ challenges and strategies in using digital media in teaching English - Urai Salam; Wahdini Wahdini; Surmiyati Surmiyati; Yanti Sri Rezeki; Dwi Riyanti; Payupol Suthathothon (UPT Bahasa Universitas Tanjungpura, 2023)
This study aimed to identify the challenges faced by teachers in integrating digital media in EFL classrooms and explore their innovative solutions to overcome them. Data were derived from interviews with teachers who attempted to incorporate digital media in a variety of situations. Official documents, including local and national government regulations, school websites, school YouTube channels, and lesson plans supplemented the interview data. The results revealed that teachers faced challenges such as lack of competence, deficient teaching materials, and inadequate digital teaching skills when attempting to integrate technology into their classroom. Limitations of infrastructures, such as low internet bandwidth and a scarcity of devices available in their schools were also reported as additional contributing challenges. Despite the difficult circumstances, evident in the study were teachers’ willingness and efforts to make use of a diverse array of technology devices and applications in their classrooms. These included projectors, laptops, smartphones, audio speakers, as well as software such as word processors, PowerPoint, Google Classroom, Hot Potatoes, search engines, WhatsApp, Zoom, Google Meet, online dictionaries, YouTube, and video editors. This study sheds light on the resilience and resourcefulness of EFL teachers in adapting to digital media and offers insights into ways to support and enhance their efforts.